Increasing Farmer Capacity Towards Protecting the Geographical Indication of Mount Ungaran Coffee - Fulia Aji Gustaman; Lelu Dina Apristiai; Wahid Akhsin Budi Nur Sidiq; Dhita Prasisca Mutiatari; Dadan Budiansyah (Universitas Negeri Semarang, 2024)
Kendal Regency is the 4th largest coffee producing area in Central Java Province with total production reaching 1,806.30 tons in 2021. Coffee production in Kendal Regency in 2021 was produced by Singorojo District amounting to 469 tons, Limbangan District amounting to 450 tons, Patean District amounting to 361 tons and Sukorejo District amounted to 322 tons. One of the coffee producing areas in Limbangan District is Ngesrepbalong Village where the majority of the type of coffee produced is robusta coffee. Based on initial observations of 17 coffee farmers who are members of the Berkah Wana Lestari coffee group in Ngesrepbalong Village, in the 2021 harvest season, the total coffee harvest reached 10.7 tonnes with a productivity level of 0.12 tonnes/ha. On average, each coffee tree in Ngesrepbalong Village produces 2 kilograms of wet coffee fruit (cherry) with a harvest ratio of once a year. The problems experienced by partners are (1) The coffee farming community does not yet know the importance of geographical indications for Mount Ungaran coffee products, there is no coffee farming community institution that focuses on inventory and documentation of geographical indications for Mount Ungaran coffee products, (2) There is no broad information base. land, productivity and detailed characteristics regarding Mount Ungaran coffee, (3) Limited equipment to support the production of organic fertilizer in coffee cultivation activities in Ngesrepbalong Village. Activities carried out by pioneering geographical indications include strengthening group institutions, facilitating facilities and infrastructure to support coffee cultivation, introducing geographical indications, participatory mapping of coffee land and preparing a geographic indication database.